Early-life gut microbiota in food allergic children and its impact on the development of allergic disease - Xiumei Yan; Jingbin Yan; Qiangwei Xiang; Huan Dai; Yinghui Wang; Lingjuan Fang; Kaiyu Huang; Weixi Zhang (BMC, 2023)
Abstract Background The prevalence of food allergies (FA) has been steadily increasing over 2 to 3 decades, showing diverse symptoms and rising severity. These long-term outcomes affect children's growth and development, possibly linking to inflammatory bowel disease. However, the cause remains unclear. Previous studies reveal that early infancy significantly impacts FA development through gut microbiota. Yet, a consistent view on dysbiosis characteristics and its connection to future allergies is lacking. We explored how early-life gut microbiota composition relates to long-term clinical signs in children with FA through longitudinal research. Methods We employed high-throughput 16S rDNA gene sequencing to assess gut microbiota composition in early-life FA children in southern Zhejiang. Follow-up of clinical manifestations over 2 years allowed us to analyze the impact of early-life gut microbiota dysbiosis on later outcomes. Results While the diversity of gut microbiota in FA children remained stable, there were shifts in microbiota abundance. Abundant Akkermansia, Parabacteroides, Blautia, and Escherichia-Shigella increased, while Bifidobacterium and Clostridium decreased. After 2 years, two of ten FA children still showed symptoms. These two cases exhibited increased Escherichia-Shigella and reduced Bifidobacterium during early childhood. The other eight cases experienced symptom remission. Conclusions Our study suggests that FA and its prognosis might not correlate with early-life gut microbiota diversity. Further experiments are needed due to the small sample size, to confirm these findings.